Perdagangan Efisien dalam Perspektif Islam: Kepentingan Simetris, Keseimbangan Informasi dan Keseimbangan Antar Sektor - Moh Khoiruddin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
Many major problems arise in the trading. All these problems could not beseparated from the conventional economic concept belief that market force will create “order” and “harmony”, and every effort for the government intervention will only lead to market distortions and inefficiency. Symmetry concept between the public and private interests that will be able to realize a good trade order and fair, also the concept of self-interest as the cornerstone of all activities, including producers / sellers and consumers. That concept has been proven to cause market distortions and inefficiency within the micro and macro. Trade sector is a special emphasis in Islamic economics, for its links directly with the real sector. The author, based on reality problems and as well as exploration of Islamic values, particularly in trade areas, recommending solutions to trade problems. First, the concept of symmetry between the private and public interests are believed to bring good order and fair trade must be changed to be symmetrical between the interests of consumers, producers / sellers and the government. Second, the government as a regulator of trade must build systems that ensure the minimization of assymetric information anytime and anywhere, which essentially includes the publication of prices and product specifications in real time, accurate, inexpensive, and informative so that all parties to avoid deception or inaccurate information. Third, the regulations should not increase the cost burden of the public or business, let alone the additional costs outweigh the benefits. Fourth, to ensure stability and economic security, the development of financial sector development should be based on the real sector, in which is dominated by the trade sector